2012
DOI: 10.1155/2012/584262
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen- and Host-Directed Anti-Inflammatory Activities of Macrolide Antibiotics

Abstract: Macrolide antibiotics possess several, beneficial, secondary properties which complement their primary antimicrobial activity. In addition to high levels of tissue penetration, which may counteract seemingly macrolide-resistant bacterial pathogens, these agents also possess anti-inflammatory properties, unrelated to their primary antimicrobial activity. Macrolides target cells of both the innate and adaptive immune systems, as well as structural cells, and are beneficial in controlling harmful inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 228 publications
1
91
0
7
Order By: Relevance
“…Binding to the A site prevents addition of an incoming amino acid-charged tRNA to the nascent polypeptide chain, aborting polypeptide growth (15). In addition to their direct antibacterial effect, macrolides are immunomodulators, presenting anti-inflammatory activities on cells of the innate and adaptive immunity and on structural cells (16)(17)(18). On airway epithelia, macrolides positively regulate tight junctions (19) and suppress the activation of NF-B, Sp1, and AP-1, leading to a reduction of proinflammatory cytokines (20)(21)(22)(23)(24)(25).…”
Section: N Ontypeable (Noncapsulated) Haemophilus Influenzae (Nthi)mentioning
confidence: 99%
“…Binding to the A site prevents addition of an incoming amino acid-charged tRNA to the nascent polypeptide chain, aborting polypeptide growth (15). In addition to their direct antibacterial effect, macrolides are immunomodulators, presenting anti-inflammatory activities on cells of the innate and adaptive immunity and on structural cells (16)(17)(18). On airway epithelia, macrolides positively regulate tight junctions (19) and suppress the activation of NF-B, Sp1, and AP-1, leading to a reduction of proinflammatory cytokines (20)(21)(22)(23)(24)(25).…”
Section: N Ontypeable (Noncapsulated) Haemophilus Influenzae (Nthi)mentioning
confidence: 99%
“…Patients with chronic P. aeruginosa lung infection are often treated with AZM because of its anti-pseudomonal and immunomodulatory properties [16,17]. Unfortunately, there is a number of patients that do not benefit from AZM therapy or that show adverse effects to the drug [18].…”
Section: Introductionmentioning
confidence: 99%
“…The macrolide antibiotic tilmicosin is a tylosin-derivative being used in treatment of respiratory diseases in different animal species. Despite the inflammatory modulating potential of macrolide members, particularly that of erythromycin, has been reported (Labro, 1998;Steel et al, 2012), however, there is no, at least for our information, any data reported about antipyretic potential of this drug group.…”
Section: Discussionmentioning
confidence: 64%